Halobacterium salinarum NRC-1 Sustains Voltage Production in a Dual-Chambered Closed Microbial Fuel Cell - Rodrigo Oliveira Goncalves; Ali Salehi; Marlon Publico; Jimmy Nyende; Nalina Nadarajah; Soheil Ghoreyshi; Padmaja Shastri (The Scientific World Journal)
Sustained bioenergy production from organisms that thrive in high salinity, low oxygen, and low nutrition levels is useful in monitoring hypersaline polluted environments. Microbial fuel cell (MFC) studies utilizing single species halophiles under salt concentrations higher than 1 M and as a closed microbial system are limited. The current study aimed to establish baseline voltage, current, and power density from a dual-chambered MFC utilizing the halophile Halobacterium salinarum NRC-1. MFC performance was determined with two different electrode sizes (5 cm2 and 10 cm2), under oscillating and nonoscillating conditions, as well as in a stacked series. A closed dual-chamber MFC system of 100 mL capacity was devised with Halobacterium media (4.3 M salt concentration) as both anolyte and catholyte, with H. salinarum NRC-1 being the anodic organism. The MFC measured electrical output over 7, 14, 28, and 42 days. MFC output increased with 5 cm2 sized electrodes under nonoscillating (p<0.0001) relative to oscillating conditions. However, under oscillating conditions, doubling the electrode size increased MFC output significantly (p=0.01). The stacked series MFC, with an electrode size of 10 cm2, produced the highest power density (1.2672 mW/m2) over 14 days under oscillation. Our results highlight the potentiality of H. salinarum as a viable anodic organism to produce sustained voltage in a closed-MFC system.